Optical screw-wrench for microassembly - Köhler, Jannis (Microsyst Nanoeng, 2017)
For future micro- and nanotechnologies, the manufacturing of miniaturized, functionalized, and integrated devices is indispensable. In this paper, an assembly technique based on a bottom-up strategy that enables the manufacturing of complex microsystems using only optical methods is presented. A screw connection is transferred to the micrometer range and used to assemble screw- and nut-shaped microcomponents. Micro-stereolithography is performed by means of two-photon polymerization, and microstructures are fabricated and subsequently trapped, moved, and screwed together using optical forces in a holographic optical tweezer set-up. The design and construction of interlocking microcomponents and the verification of a stable and releasable joint form the main focus of this paper. The assembly technique is also applied to a microfluidic system to enable the pumping or intermixing of fluids on a microfluidic chip. This strategy not only enables the assembly of microcomponents but also the combination of different materials and features to form complex hybrid microsystems.